A 600V PiN diode with partial recessed anode and double-side Schottky engineering for fast reverse recovery. (April 2019) - Li, Shaohong; Zhang, Long; Zhu, Jing; Tang, Qingxi; Sun, Ling; Wang, Hao; Tong, Xin; Sun, Weifeng
Abstract: In this paper, a novel 600 V PiN diode for fast recovery is proposed and the operation mechanism as well as the high dynamic ruggedness of the device are analyzed in detail. The proposed structure features the alternating P/N region with partial recessed P region at anode side and the P Schottky as well as the N Schottky contacts at both sides. In on-state, the carrier injection efficiency can be modulated by adjusting the work function of the anode P Schottky contact (WSA ), which is based on MSC (Metal-Semiconductor-Contacts) concept. As a result, the fast recovery is realized due to the reduced amount of the stored carriers and the shortened carrier extraction path. In off-state, the leakage current can be effectively suppressed attributed to the rapid pinch-off of the depletion layer. The forward voltage drop (VF ) and the reverse recovery time (trr ) of the proposed structure can be adjusted by changing the depth of the P Schottky contact (tra ) on the sidewall, without sacrificing the breakdown voltage (BV). The proposed structure achieves a trr of 75ns which is 45.7% and 33% lower than that of the conventional PiN and the MPS structure at the same VF of 0.965 V, respectively. Moreover, the total amount of holes in the N buffer layer can be supplemented by adjusting the work function of the cathode N Schottky contact (WSC ) during reverse recovery, resulting in a high-dynamic ruggedness with suppressed voltage oscillation and voltage overshoot. Highlights: In on-state, the carrier injection efficiency can be modulated by adjusting the work function of the anode Schottky contact. In off-state, the leakage current can be effectively suppressed attributed to the rapid pinch-off of the depletion layer. The fast recovery is realized due to the reduced amount of the stored carriers and the shortened carrier extraction path. The suppressed voltage oscillation and voltage overshoot is realized due to the existence of cathode Schottky contact.